Innovation and Entrepreneurship : Theory, Policy and Practice - Carayannis, Elias G.; Samara, Elpida T.; Bakouros, Yannis L. (Innovation, Technology, and Knowledge Management, 2015)
This book aims to meet the needs of education and training in modern techniques of innovation and entrepreneurship, and focuses on the detailed presentation of successful business practices. As today's global economic landscape is changing rapidly, the ability of businesses to introduce new products and services to the market faster than their competitors is perhaps their most distinct competitive advantage. This becomes obvious by the significant market share that the most innovative companies gain while increasing profitability. Extensive research in this field has demonstrated that companies that are constantly innovating normally double their profits compared to others. Moreover, establishing successful practices and policies of innovation management, through which ideas evolve from conception through evaluation to implementation and commercialization, become the basis for economic growth at the firm, industry, national, regional, and global levels. Taking Greece as an example, this volume identifies systemic weaknesses in development of new products, risk capital, patenting, broadband penetration, lifelong training, investment in research on the part of firms, high-tech exports, and employment in medium-high-technology manufacturing that place the country at the bottom of the European Union in economic performance and threaten its potential to achieve sustainable growth. To address these weaknesses in Greece and similar countries around the world, the authors present a comprehensive overview of the principles of innovation and entrepreneurship, with particular respect to their relationships to knowledge, learning, and creativity. Drawing from a strong theoretical foundation, and illustrated through in-depth case studies and examples from both private and public sectors, the authors present a framework for innovation management that integrates research, education, practical application, and policy. Specific topics include technology transfer, intellectual property rights management, the practice of knowledge management intellectual capital investment, business incubators, and Cooperation Research and Development Agreements (CRADAs).